2019
DOI: 10.1111/ajo.13048
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term patient‐reported outcomes after laparoscopic Burch colposuspension

Abstract: Background:The negative media attention surrounding vaginal mesh procedures has seen a rise in demand for minimally invasive non-mesh options for the treatment of stress urinary incontinence (SUI). The laparoscopic Burch colposuspension (LBC) is a non-mesh alternative to synthetic midurethral slings (MUS) with similar short-term outcomes. However, long-term outcomes are not well established. Aims:To evaluate the long-term outcomes of LBC for treatment of SUI in women. Material and Methods: One hundred and fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Sivaslioglu et al and Bandarian et al reported similar results with operation time for the TOT procedure of 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) min and the mean hospital stay in the TOT group was 2.06 ± 1.03 days [5,17]. Ulmsten U. et Petros P. reported similar results in their study [13].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Sivaslioglu et al and Bandarian et al reported similar results with operation time for the TOT procedure of 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) min and the mean hospital stay in the TOT group was 2.06 ± 1.03 days [5,17]. Ulmsten U. et Petros P. reported similar results in their study [13].…”
Section: Discussionsupporting
confidence: 54%
“…Regarding cure rate after the laparoscopic Burch procedure, our study reported a cure rate of 66.2% in the modified laparoscopic Burch group. In their research, Conrad et al reported higher subjective success rates, with 78.1% of patients reporting no symptoms of SUI at a mean follow-up of 50.6 months and 12.4% reporting significantly improved symptoms in the laparoscopic Burch group [ 18 ]. Yang et al described their high results with a laparoscopic Burch group with 116 of 155 women available at 1-year follow-up with an objective cure rate 94.8% (110/116) and a subjective cure rate 95.7% (110/116) [ 19 ], and Hong et al reported a 72.1% cure rate in their laparoscopic Burch group [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Burch is more traumatic, and may also be complicated by acute urinary retention, retropubic hematoma, and pubic osteitis, etc. It requires advanced operating skills and increases the incidence of prolapse of the posterior wall of the vagina and the fornix 12,13 . Therefore, the mid‐urethral linear suspension surgery has the clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…It requires advanced operating skills and increases the incidence of prolapse of the posterior wall of the vagina and the fornix. 12,13 Therefore, the mid-urethral linear suspension surgery has the clinical significance. The difference between mid-urethral linear suspension and Kelly plication, is making a hammock below the urethra and plicating the 'relaxed tissues at the vesical neck'.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Conrad et al reported that 90% of patients who underwent Burch colposuspension showed successful treatment with a mean follow-up of 50 months (13-89 months). They defined successful treatment as a subjective cure or significant improvement of SUI [23].…”
Section: Time To Rethink Traditional Sui Surgeries: Clinical Outcomesmentioning
confidence: 99%